Treatment of tooth fracture by medium-energy CO 2 laser and DP-bioactive glass paste: the interaction of enamel and DP-bioactive glass paste during irradiation by CO 2 laser - Lin, Chun-Pin; Tseng, Ya-Chun; Lin, Feng-Huei; Liao, Jiunn-Der; Lan, Wan-Hong (Biomaterials, 2001)
Acute trauma or trauma associated with occlusal disturbance can produce tooth crack or fracture. Although several methods are proposed to treat the defect, however, the prognosis is generally poor. If the fusion of a tooth fracture by laser is possible, it will offer an alternative to extraction or at least serve as an adjunctive treatment in the reconstruction. We have tried to use a continuous-wave CO 2 laser and a newly developed DP-bioactive glass paste (DPGP) to fuse or bridge tooth crack or fracture lines. Both the DP-bioactive glass paste and tooth enamel have strong absorption bands at the wavelength of 10.6 μm. Therefore, under CO 2 laser, DPGP and enamel should have an effective absorption and melt together. The interface between DPGP and enamel could be regarded as a mixture of DPGP and enamel (DPG–E). The study focused on the phase transformation, microstructure, functional group and thermal behavior of DPG–E with or without CO 2 laser irradiation, by the analytical techniques of XRD, FTIR, DTA/TGA, and SEM. The results of XRD showed that the main crystal phase in the DPG–E was dicalcium phosphate dihydrate (CaHPO 4·2H 2O). It changed into CaHPO 4, γ-Ca 2P 2O 7, β-Ca 2P 2O 7 and finally α-Ca 2P 2O 7 with increasing temperature. In the FTIR analysis, the 720 cm −1 absorption band ascribed to the P–O–P linkage in pyrophosphate rose up and the intensities of the OH − bands reduced after laser irradiation. In regard to the results of DTA/TGA after irradiation, the weight loss decreased due to the removal of part of absorption water and crystallization water by the CO 2 laser. SEM micrographs revealed that the melted masses and the plate-like crystals formed a tight chemical bond between the enamel and DPGP. We expect that DPGP with the help of CO 2 laser can be an alternative to the treatment of tooth crack or fracture.